Effect of environmental temperature and an inoculant on the fermentation of forage sorghum silage - Bolsen, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The inoculants, BioPower®, increased the rate and efficiency of ensiling in Acco Paymaster 351 forage sorghum regardless of storage temperature. The untreated, 60 F silage fermentated slower and had higher pH, lower lactic acid, and higher acetic acid values than its 90 F counterpart.
Keywords: Beef; Inoculant; Fermentation; Sorghum silage